Using activating methods of teaching artistic design to future interior designers - Nadezhda S. Zhdanova; Anna V. Ekaterinushkina; Yuliya S. Antonenko (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
Management of student learning has always been in the field of view and discussion of teachers. Today, a lot of diverse experience has already been accumulated; it is presented in a number of publications by different authors. At the same time, the topic is far from being exhausted, because the content of the activity itself makes its own contribution to any methods and recommendations. Each subject area of activity has its own preferences in the use of activating methods, their combinations and places of application. These features have not been sufficiently studied in the professional training of future designers. The purpose of the study is to test the influence of activating teaching methods, thanks to which students intensively master the process of artistic design and demonstrate fairly high results. Preliminary experience in studying the topic indicates that the teacher introduces activating methods into the educational process, and the student, under their influence, successfully develops and performs educational tasks with high quality. To study the influence of activating methods, experimental work was carried out with students studying design. The stages of design and the corresponding methods of the teacher’s activity are considered, which cause the activation of students and lead to an increase in the effectiveness of completed projects, and therefore to a higher quality of professional training.